Critical Reasoning in Chemical Bonding: A Study of Students’ Responses to Higher-Level Thinking Questions - Dwi Melani Putri; Hartono Hartono (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Critical Reasoning in Chemical Bonding: A Study of Students’ Responses to Higher-Level Thinking Questions. Purpose: To analyze students' critical thinking skills in solving HOTS questions on chemical bonding and identify the dominant Ennis indicators. Method: This quantitative descriptive study involved 34 students at SMA Srijaya Negara Palembang (2025/2026) selected via purposive sampling. Data were collected through 8 HOTS essay items and interviews. Findings: Achievement in providing simple explanations reached 73.40%, concluding 68%, and providing further explanations 61%, all in the moderate category. The overall average score was 67.47% (moderate). Conclusion: Students' critical thinking skills in chemical bonding are categorized as moderate, with "providing simple explanations" as the most dominant indicator.